On the Local Formation of the TRAPPIST-1 Exoplanets - Matthew S. Clement; Elisa V. Quintana; Kevin B. Stevenson (The Astronomical Journal)
The discovery of seven approximately Earth-mass planets orbiting the 0.09 M _⊙ M dwarf TRAPPIST-1 captivated the public and sparked a proliferation of investigations into the system’s origins. Among other properties, the resonant architecture of the planets has been interpreted to imply that orbital migration played a dominant role in the system’s early formation. If correct, this hypothesis could imply that all of the seven worlds formed far from the star, and might harbor enhanced inventories of volatile elements. However, multiple factors also contradict this interpretation. In particular, the planets’ apparent rocky compositions and nonhierarchical mass distribution might be evidence that they formed closer to their current orbital locations. In this paper, we investigate the latter possibility with over 600 accretion simulations that model the effects of collisional fragmentation. In addition to producing multiple TRAPPIST-like configurations, we experiment with a number of different models for tracking the evolution of the planets’ volatile contents and bulk iron-to-silicate ratios. We conclude that a trend in bulk iron contents is the more likely explanation for the observed radial trend of decreasing uncompressed densities in the real system. Given the degree of radial mixing that occurs in our simulations, in most cases we find that all seven planets finish with similar volatile contents. Another confounding quality of the TRAPPIST-1 system is the fact that the innermost planets are not in first-order resonances with one another. By applying a tidal migration model to our most promising accretion model results, we demonstrate cases where higher-order resonances are populated.